Pemberdayaan Siswa Dalam Menggapai Prestasi Akademik Tingkat Kabupaten Di SDN 1 Ceper Klaten - Kurniawan, Aditya Arief; , Dr. Sabar Narimo, M.M, M.Pd; , Dr. Achmad Fathoni (2016)
Aditya Arief Kurniawan. Q. 100 140 157. Empowering Students in Achieving Academic Achievement District Levels at SDN 1 Ceper Klaten. Thesis Graduate School of Surakarta Muhammadiyah University, 2016. This study aims to determine the role of the principal in attaining academic achievement district level. Then further determine the role of teachers in achieving academic achievement district level. And then knowing Activities of students in achieving academic achievement district level. This type of method used in this study is a qualitative research design using an ethnographic approach. In this study using data sources from interviews, observation and documentation relating to the role of principals and teachers as well as students' activity in attaining academic achievement district level. Sources of data in this research shall be composed of informants, event or occurrence, and documentation. he results showed that, Leadership principal of SDN 1 Ceper in managing human resources based on the achievements made through the planning, organizing, implementing, and controlling HR. The role of teachers at SDN 1 Ceper in order to empower the students shown by guiding and directing the activities of students in accordance with the objectives aspired. Student activities SDN 1 Ceper in achieving academic achievement among district level by participating actively and sincerely in coaching.